Current role of transarterial chemoembolization and radioembolization in the treatment of metastatic colorectal cancer. (April 2014) - Bester, Lourens; Meteling, Baerbel; Boshell, David; Saxena, Akshat; Morris, David L
SUMMARY  In this article, we review two liver-directed therapies that are currently used for the palliative treatment of primary and secondary hepatic malignancies, transcatheter arterial chemoembolization (TACE), including a new type of TACE with drug-eluting beads, and radioembolization. Important developments and administration techniques for all therapies are discussed, as well as their integration into the current routine clinical care for management of metastatic colorectal cancer. According to published data from clinical trials, as presented in this review, both radioembolization and TACE/TACE with drug-eluting beads have been proven to be safe and effective in selected patients with chemorefractory liver metastases from colorectal cancer. For patients with unresectable liver-only or liver-dominant disease who have failed standard chemotherapy options or for whom chemotherapy is contraindicated, new modalities, such as those discussed, are particularly valid and promising if clinical guidelines for patient selection and treatment administration are followed.